(untitled) (African Journal of Biomedical Research, 2023)
Malaria infection during pregnancy is a significant public health problem with substantial risks for the pregnant woman, her fetus and the newborn child.This study was conducted to determine the prevalence of malaria parasite infection and associated risk factors among pregnant women in Mbaitoli Local Government Area of Imo State. A total of 300 pregnant women were sampled for malaria parasites infection using thick and thin film smears. Venous blood samples of 1ml were collected from pregnant women attending antenatal clinic in Primary Health Care Centres and hospitals using needles and syringes to determine the presence of malaria parasite. Questionnaires were also filled. Data was analysed using simple percentages, Odd ratios and Chi-square analytical statistical tools. An overall prevalence of 63.7% was recorded in the study, while the proportions of women infected were highest within the 26-30 years age cohort (73.5%) . The burden of malaria infection among pregnant women in Mbaitoli Local Government Area is significant across the various examined depended variables which implies that malaria remains one of the highest prevalent diseases facing pregnant women. Age, Educational status, Occupational status, presence of stagnant water around the surrounding residence, overgrown weeds/bushes around the residence, non-use of mosquito insecticide nets, staying late-night , not attending antenatal care and health education sessions are significantly associated with malaria infection in the area. Effort should be geared towards improving their environmental conditions and educational backgrounds. Insecticide treated mosquito nets should be provided.